GAMBARAN OPTIMISME PADA PASIEN DIALISIS - Fauziah Zahra; Ulfiah Ulfiah; Irfan Fahmi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
This research aims to know the description of optimism from one of dialisys patient. Qualitative methodology with case study has been done since April 2011. Result shows that subject has high optimism since he has characteristics of being optimist person. Factors causing D being optimist arised from self-faith and family suport like husband and her children. Besides, hospital environment also give positive input and make D keep survive.